Profile of Science Process Skills in Class XI Learners in the Implementation of the POGIL Model on Static Fluid Material - Alfiah, Isnur; Salam, Abdul; Haryandi, Surya (Universitas Lambung Mangkurat, 2025)
The lack of experimental methods in physics learning causes students in one of the public high schools in Banjarmasin City to have low scores for science process skills (SPS). The teacher's results also corroborate this needs analysis, which shows the need to implement learning that supports the development of SPS. Therefore, the purpose of this study is to describe the SPS profile of students through the implementation of the POGIL model. The research method is categorized as quantitative research using a pre-experimental design. Data collection techniques regarding the SPS profile of students were carried out using the SPS observation sheet instrument by observers. The data analysis technique used was descriptive quantitative. The average achievement results for each SPS indicator are as follows: formulating problems 98.61; formulating hypotheses 93.52; identifying variables 57.41; conducting experiments 82.41; analyzing data 91.20; and drawing conclusions 74.54. Based on the results of this study, implementing the POGIL model is effective in training students' SPS. Overall, the study showed that the approach used improved learners' SPS and facilitated active and collaborative learning. This is highly relevant for educators and curriculum developers designing more effective learning experiences in science. Future research is expected to emphasize the SPS indicators and better organize students to play a more active role in learning activities.